ADVANTAGES AND DISADVANTAGES OF MALE CIRCUMCISION TECHNIQUES: A LITERATURE REVIEW - Andersen; Shannen, Felicia Adelina; Mataram, Ridwan (Indonesian Urological Association, 2021)
Objective: To compare the advantages and disadvantages of male circumcision techniques. The articles of male circumcision techniques were investigated from October 2018 to December 2018 through Google Scholar and Proquest. Material & Methods: There are various methods of circumcision, these methods can be grouped into two: using shield and clamp devices and conventional methods (dorsal slit and excision). Results: The result from this review article are the technique using shield and clamp devices such as the Smart Klamp have several advantages, that are minimal bleeding, rarely injuring the glans penis and faster, but the disadvantage is taken more costs, and often occurs edema in the circumcision area. Conclusion: In general, the circumcision method using shield and clamp devices is more beneficial and more practical than conventional methods.